Pregnancy outcome in women with polycystic ovary syndrome - V. S., Nivedhitha; R., Sankareswari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To compare the pregnancy outcome in polycystic ovary syndrome (PCOS) women with normal women and to study the incidence of pregnancy complications like spontaneous abortions, preterm labour, gestational diabetes, gestational hypertension, preeclampsia, pregnancy and neonatal outcome in women with PCOS. Methods: Prospective comparative study done on 160 pregnant women to compare the pregnancy outcome in PCOS and normal women. All patients were subjected to detailed history, general and obstetric examination, antenatal investigations, routine dating scan, glucose challenge test at 24 to 28 weeks in study and control groups, blood pressure recording and urine for proteinuria after 20 weeks to evaluate preeclampsia. After delivery, birth weight and apgar score at 1 and 5 minutes are recorded. Body mass index is calculated and pregnancy outcome studied and compared. Results: Out of 80 pregnancies with PCOS, 8 had spontaneous abortions, 11 Gestational diabetes mellitus (GDM), 9 gestational hypertension, 5 preeclampsia and 3 had preterm labour. GDM is 3 times, Spontaneous Abortion is 4.33 times, gestational hypertension is 3.25 times and neonatal intensive care unit (NICU) admission is 3.25 times more in PCOD women. Conclusions: Pregnancy complications like spontaneous abortions, gestational diabetes, gestational hypertension and neonatal complications requiring NICU admissions are significantly higher in pregnant women with PCOD. Pregnant women with PCOD may become a high risk pregnancy at any time. Hence proper antenatal care is mandatory to prevent and treat the complications.